ARTIFICIAL NAILS... VERY REAL RISKS - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2002)
Should OR personnel scrub while wearing artificial nails? This question is currently being discussed in many operating room departments. This article will discuss the types of artificial nails available, and how they are applied. Effects of hand cleaning on artificial nails and barrier properties of surgical gloves will also be investigated. Documented transmissions of infection related to artificial nails will also be discussed.